2005
DOI: 10.1111/j.1467-8373.2005.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation costs: Nature-based tourism as development at Cuc Phuong National Park, Vietnam

Abstract: Local communities are frequently displaced from areas selected for environmental protection. Development of nature-based tourism, believed to be more environmentally benign than traditional agricultural systems, has been encouraged by governments and national park managers in the hope of providing alternative livelihoods for local people. This paper examines the extent to which indigenous peoples resettled from within one Vietnamese national park have engaged with the nascent tourism industry, thereby providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Such conflicts between local interests and tourism-associated demands are not unique to Machu Picchu (e.g. Rugendyke & Son, 2005). The ICOMOS highlights the difficulties in integrating cultural resource management and tourism in its International Cultural Tourism Charter, asserting that physical, intellectual and emotive access to cultural heritage sites is a right that should not be denied (ICOMOS, 1999).…”
Section: Persistence Of Peruvian Culturementioning
confidence: 97%
“…Such conflicts between local interests and tourism-associated demands are not unique to Machu Picchu (e.g. Rugendyke & Son, 2005). The ICOMOS highlights the difficulties in integrating cultural resource management and tourism in its International Cultural Tourism Charter, asserting that physical, intellectual and emotive access to cultural heritage sites is a right that should not be denied (ICOMOS, 1999).…”
Section: Persistence Of Peruvian Culturementioning
confidence: 97%
“…Other studies found no evidence that respondents felt that either negative or positive impacts resulted from the protected area [75,86,88,91,92].…”
Section: Society and Developmentmentioning
confidence: 99%
“…SUF regulations prevent all extractive and most non‐extractive resource uses and specify that protected lands should be managed to address four objectives: 1) the preservation of nature, 2) the protection of historical and cultural sites, 3) scientific research, and 4) recreation/tourism. Although the Ministry of Agriculture and Rural Development (MARD) is responsible for the overall direction of SUFs, oversight of individual SUFs is provided by local management boards (Rugendyke and Son ). Overlapping agency jurisdictions sometimes create confusion.…”
Section: Growing a System Of National Parksmentioning
confidence: 99%